CONVICÇÕES DE SAÚDE E CÂNCER INFANTIL: UM ESTUDO DE FAMILIARES EM CASAS DE APOIO - Dias, Ana Luiza (2016)
Cancer is the main pathology responsible for deaths among children and adolescents in Brazil and the estimate shows that there is a growing incidence of new cases year after year. The treatment for this chronic disease is long, painful and distressing and the possibility of death follows the patient and family all the time in this process. Besides, the health care network in many regions of our country is not prepared to provide the necessary services for this population, therefore, children and caregivers are transferred to cancer centers of reference which are often indeed far from their homes. Therefore, the objectives of this study are aimed at the description of the health beliefs of caregivers of children with cancer welcomed by support houses of São Paulo and to understand the influence that this health beliefs have on the role of caregiver. 10 women were interviewed, mostly mothers of infants aged from 04 to 13 years who were under treatment for cancer or in remission and control period. The collected data were analyzed according to the research model in "health beliefs" which assesses the impact of the diagnosis, susceptibility, severity, benefits, barriers, self-efficacy and expectations for the future according to the perception of each caregiver. The results show that from diagnosis until the last visit of the control period anguish, anxiety, insecurity and fear are present in the routine of these women and the distance of their homes, the extended family and their everyday activities is a factor that significantly aggravates the intense suffering that this experience cause. From these results it is recommended that more psychosocial care from multidisciplinary teams of support houses and health care network in order to lessen the emotional burden and reduce the psychological damage caused by cancer and their processing. It is expected that changes in this area allow families a better living with the disease and the inevitable transfer to oncology centers, as well as re-establish basic aspects of quality of life of children cancer patients caregivers.